2015
DOI: 10.1158/1940-6207.capr-15-0119
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Bioavailability and Chemopreventive Activity in Women Scheduled for Breast Biopsy

Abstract: Epidemiological studies suggest a protective effect of cruciferous vegetables on breast cancer. Sulforaphane (SFN), an active food component derived from crucifers, has been shown to be effective in breast cancer chemoprevention. This study evaluated the chemopreventive effect of SFN on selective biomarkers from blood and breast tissues. In a 2-8-week double-blinded, randomized controlled trial, 54 women with abnormal mammograms and scheduled for breast biopsy were randomized to consume a placebo or a glucorap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 47 publications
1
96
0
Order By: Relevance
“…In both studies, the time for the intervention was similar, namely 20 and 24 weeks, respectively, but the amount of SFN was much higher in the work of Cipolla et al [46], and that probably favored the better more encouraging final results in this study. In any case, Atwell et al [47] planned to evaluate the efficacy of the consumption of the broccoli sprouts extract to modify the activity of the HDAC (histone deacetylase) and the breast tumor marker CA (carcinogenic antigen) in order to improve the diagnosis in women with benign disease and non-invasive CA. They proposed an intervention using six pills with a theoretical content of SFN of 30 mg in three administrations per day.…”
Section: Medium-length Studiesmentioning
confidence: 99%
“…In both studies, the time for the intervention was similar, namely 20 and 24 weeks, respectively, but the amount of SFN was much higher in the work of Cipolla et al [46], and that probably favored the better more encouraging final results in this study. In any case, Atwell et al [47] planned to evaluate the efficacy of the consumption of the broccoli sprouts extract to modify the activity of the HDAC (histone deacetylase) and the breast tumor marker CA (carcinogenic antigen) in order to improve the diagnosis in women with benign disease and non-invasive CA. They proposed an intervention using six pills with a theoretical content of SFN of 30 mg in three administrations per day.…”
Section: Medium-length Studiesmentioning
confidence: 99%
“…On Day 0 of the study, dogs were orally administered three capsules of a broccoli sprout supplement (BroccoMax TM ) to achieve 90 mg total of GFN (per Jarrow Formulas Ăą , 30 mg of GFN yields 8 mg SFN in vitro). The GFN dose used was based on estimated weight equivalent dose in people (Atwell et al 2015a). All dogs swallowed the supplement without chewing, and received their morning meal immediately following the broccoli sprout supplement dosing (BroccoMax TM ).…”
Section: Dietary Interventionmentioning
confidence: 99%
“…Moreover, a recent human clinical study suggested that this compound was not an effective antagonist of the hPXR in vivo [43]. Considering the antagonistic effect on PXR of SFN at relative high concentrations in vitro and its other pharmacologic activities, such as histone deacetylase inhibition [44], achieved at relatively lower concentrations, further investigation of the on-target effect of SFN against PXR is warranted, especially at physiologically relevant concentrations.…”
Section: Pxrmentioning
confidence: 99%